Bile duct ligation impairs visual acuity in rats by ammonia- and bilirubin-induced retinal degeneration - Yang Yi-ting; Ji Ming-rui; Lin Zi-jin; Li Ping; Wu Run-ze; Liu Xiao-dong; Liu Li (Acta Pharmacologica Sinica, 2025)
Patients with hepatic failure are often accompanied by hepatic retinopathy, but the cellular and molecular mechanisms underlying the hepatic retinopathy remain unclear. In this study, we investigated how liver failure leads to hepatic retinopathy using bile duct ligation (BDL) rats as a cholestasis animal model. Light-dark box test was used to assess sensitivity to light, indexed as visual acuity. On D28 post-BDL, rats were subjected to light-dark box test and blood samples were collected for biochemical analyses. The rats then were euthanized. Liver, spleen and both side of eye were quickly harvested. We showed that BDL impaired rat sensitivity to light, significantly decreased the thickness of inner nuclear layer (INL), outer nuclear layer (ONL) and total retina, as well as the retinal cell numbers in ONL and ganglion cell layer (GCL). The expression of rhodopsin (RHO), brn-3a and GPX4 was significantly decreased in retina of BDL rats, whereas the expression of cleaved caspase 3, 8, 9, bax/bcl-2, RIP1, GFAP, and iba-1, as well as TUNEL-positive cells were significantly increased. In cultured retinal explant, we found that NH4Cl (0.2, 1, 5 mM) concentration-dependently impaired activity of retinal explant, decreased thickness of INL and ONL, downregulated expression of brn-3a, RHO and GFAP, increased expression of cl-caspase 3 and TUNEL-positive cell numbers, with NH4Cl (5 mM) almost completely disrupting the structure of the cultured retina; bilirubin (1 μM) significantly upregulated GFAP expression, whereas high level (10 μM) of bilirubin downregulated expression of GFAP. We further demonstrated in vivo that hyperammonemia impaired rat sensitivity to light, decreased thickness of INL and ONL, downregulated expression of RHO, brn-3a, GFAP and increased expression of cl-caspase 3; hyperbilirubinemia impaired rat sensitivity to light, upregulated expression of GFAP and iba-1. In conclusion, BDL impaired rat visual acuity due to the elevated levels of ammonia and bilirubin. Ammonia induced loss of retinal ganglion cells and rod photoreceptor cells via apoptosis-mediated cell death. Bilirubin impaired retinal function via activating microglia and Müller cells.